Juvenile dermatomyositis in Oman: clinical patterns and disease trajectory from a National cohort - Reem Abdwani; Mahadev J. Mal; Eman Al Masroori; Ruqaiya Al Jashmi; Safiya Al Abrawi; Ibrahim Al-Zakwani (Pediatric Rheumatology Online Journal)
Abstract Objective Juvenile dermatomyositis (JDM) is an uncommon autoimmune condition in children, often leading to prolonged disease burden and significant morbidity. Despite global advancements in understanding JDM, studies from the Middle East, particularly Oman, remain scarce. This study aims to characterize JDM from an Omani national cohort, evaluating clinical manifestations, laboratory features, disease course, and treatment outcomes. Methods A retrospective review of all JDM patients diagnosed and managed by pediatric rheumatologist in tertiary centers in Oman was conducted. Patient demographics, clinical features, laboratory findings, treatment modalities, and disease outcomes were analyzed. Results A total of 30 children diagnosed with JDM were included. They had an equal female to male distribution, 1:1 ratio. The median age at disease onset was 6.78 years (range: 2–13), with a median diagnostic delay of 8.4 months (range:1–23). The median follow-up period for these patients was 4 years (absolute range: 1 month-16 years). Classic JDM skin manifestations, including heliotrope rash (n = 25; 83%) and Gottron’s papules (n = 23; 77%), were common. Proximal muscle weakness was observed in 28 (93%) patients, while 23 (77%) patients exhibited elevated muscle enzymes. MRI findings consistent with myositis were present in 70% (n = 19/27) of the subjects, and muscle biopsy confirmed JDM in 9 cases (30%). Among 25 patients tested for myositis specific antibodies, NXP2 (n = 3), Anti-TIF1 (n = 2), Anti-Mi-2 (n = 1), and MDA5 (n = 1) were detected, showing expected correlations with disease phenotype. Corticosteroids were universally administered, with methotrexate (n = 25; 83%) and IVIG (n = 15; 50%) as common adjuncts. Calcinosis was observed in 8 patients (27%), and was managed with various treatment modalities including pamidronate (n = 3), diltiazem (n = 2), and infliximab (n = 1). At the last follow-up, 18 patients (60%) were in clinical remission, 50% (n = 15) followed a polyphasic or chronic disease course, and 2 patients succumbed to disease-related complications. Conclusions This study provides comprehensive characterization of pediatric JDM in Oman. The findings highlight regional variations in disease presentation, autoantibody profiles, and treatment responses, underscoring the need for early diagnosis and individualized management strategies. Continued follow-up is essential to optimize long-term outcomes and improve survival rates in this patient population.